BEM-ESTAR SUBJETIVO E DESEMPENHO ACADÊMICO EM ESTUDANTES UNIVERSITÁRIOS - Ana Paula Domeneghetti Parizoto Fabrin; Camélia Murgo Mansao (Universidade do Oeste Paulista, 2014)
This study aimed to examine correlations between academic performance and subjective wellbeing from the perspective of Positive Psychology, which helps with definitions of the construct "Subjective Well-Being", its implications on academic performance, and professional self-efficacy beliefs. Comparisons by gender were raised in this study. A sample of students from two courses of University of São Paulo, whose measuring instruments contemplated Scale Positive and Negative Affects Zanon (EAZ) and the verification of academic performance the global averages of two semesters was formed. The results showed that no correlations between mean scores of college students with positive and negative affect components of subjective well-being assessed by EAZ were found, comparing the initial hypotheses of the research. Already notes correlated with each other. Was also indicated no differences between the means, statistically, in relation to gender.